2010
DOI: 10.1016/j.jsbmb.2010.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and subnuclear distribution of the regulatory machinery during 1α,25-dihydroxy vitamin D3-mediated transcriptional upregulation in osteoblasts

Abstract: The architectural organization of the genome and regulatory proteins within the nucleus supports gene expression in a physiologically-regulated manner. In osteoblastic cells ligand activation induces a nuclear punctate distribution of the 1α,25-dihydroxy vitamin D3 (1α,25(OH)2D3) receptor (VDR) and promotes its interaction with transcriptional coactivators such as SRC-1, NCoA-62/Skip, and DRIP205. Here, we discuss evidence demonstrating that in osteoblastic cells VDR binds to the nuclear matrix fraction in a 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The first to hypothesize that osteoblasts coordinate osteoclast activity were Rodan and Martin [55], who elegantly depicted a model in which the osteoblasts responded to some osteoclast-seeking signals, first PTH and vitamin D3, stimulating bone resorption [56,57]. This theory has been fully confirmed by subsequent studies that discovered the many underlying pathways, including the RANKL/RANK axis and the various proosteoclastogenic and pro-inflammatory cytokines, such as IL-1, IL-6, IL-11, inhibin Aβ, and tumor necrosis factor-α, among others [28•].…”
Section: Bone-cell Cross-talkmentioning
confidence: 99%
“…The first to hypothesize that osteoblasts coordinate osteoclast activity were Rodan and Martin [55], who elegantly depicted a model in which the osteoblasts responded to some osteoclast-seeking signals, first PTH and vitamin D3, stimulating bone resorption [56,57]. This theory has been fully confirmed by subsequent studies that discovered the many underlying pathways, including the RANKL/RANK axis and the various proosteoclastogenic and pro-inflammatory cytokines, such as IL-1, IL-6, IL-11, inhibin Aβ, and tumor necrosis factor-α, among others [28•].…”
Section: Bone-cell Cross-talkmentioning
confidence: 99%
“…Confirmation of the punctate intranuclear localization of the RUNX transcription factor by time-lapse fluorescence microscopy of cells with a fluorescent-tagged RUNX protein provides in situ validation of the punctate intranuclear organization [62]. Similar punctate intranuclear distribution has been confirmed for the vitamin D receptor (VDR) and co-regulatory molecules in bone-related cells [63, 64], indicating that transcriptional control of osteoblastic genes in response to vitamin D is also architecturally organized.…”
Section: Introductionmentioning
confidence: 81%
“…This VDR/SRC‐1/p300 complex brings into place the intrinsic histone acetyl transferase activity of both SRC‐1 and p300 coactivators (Carvallo et al, 2007; Kim et al, 2005), which can then mediate the increased histone acetylation that has been shown as critical during 1,25(OH) 2 D 3 dependent CYP24A1 transcription activation (Moena et al, in press). Additionally, VDR‐containing complexes can activate transcription by directly interacting with the RNA polymerase II holoenzyme at target gene promoters (Arriagada et al, 2010; Chiba, Suldan, Freedman, & Parvin, 2000; Sutton & MacDonald, 2003), including CYP24A1 (Carvallo et al, 2008; Montecino et al, 2007).…”
Section: Discussionmentioning
confidence: 99%